36.2k views
5 votes
HELP PLEASE !!!!!!!!!!!

HELP PLEASE !!!!!!!!!!!-example-1

1 Answer

2 votes

Answer:

option B

Explanation:


\lim_(x\to \infty) f(x) = \lim_(x \to \infty) (log(x+2)-3 )


= \lim_(x \to \infty) ( log(x+2)) - \lim_(x \to \infty) 3\\\\=\infty - 3\\\\= \infty


\lim_(x \to 2) f(x) = \lim_(x \to 2) ( log(x+2)) - \lim_(x \to2) 3\\\\


= log( 2 + 2 ) - 3\\\\= log 4 - 3\\\\=log(2^2) -3\\\\=2 log 2 -3


\lim_(x \to -2) f(x) = \lim_(x \to -2) ( log(x+2)) - \lim_(x \to -2) 3\\\\
\lim_(x \to -2)_+ f(x) = \lim_(x \to -2_+) ( log(x+2)) - \lim_(x \to -2_+) 3 = -\infty\\\\\lim_(x \to -2_-) f(x) = \lim_(x \to -2)_- ( log(x+2)) - \lim_(x \to -2)_- 3 = -\infty\\\\\\\lim_(x \to -2) f(x) = - \infty

User Roberto Maldonado
by
4.6k points